Incidence Of Constipation Viewed From The Regularity Of Consumption Fe Tablet In The Class Of Pregnant Women In Klantingsari Village, Tarik Sidoarjo District - Erma Retnaningtyas; Ardiniwati; Andariningsih; Tutik Nushah (Journal of Health Science Community, 2023)
Lack of iron pregnant women cause anemia so that the supply of oxygen to the fetus is reduced. Sources of iron, among others, are found in the liver of cows, kidneys, poultry, fish, soybeans, shellfish, fruit, egg yolks, wheat juice and sugar syrup. Based on the initial survey conducted January 2023 on 10 respondents in Klantingsari Village, Tarik District, Sidoarjo Regency, it can be concluded that the incidence of constipation in pregnant women. This research is correlation analytic survey research with cross sectional approach. The population in this study were all trimester II and III pregnant women who visited the Class of Pregnant Women Klantingsari Village, Tarik District, Sidoarjo Regency in 2023, sampling using the accidental sampling method with the number of 48 respondents. The instrument used was a checklist. The results of the study were tested using the chi squares test. Based on the degree of freedom (df) = 1 with a significance level of 0.05 The results of calculations from the Statistical Test of the chi square obtained p value 0.001 so that the value <α (0.001 <0.05), then H0 is rejected and H1 is accepted, so there is a relationship between regular consumption Fe tablets with constipation in pregnant women. Therefore, it should be balanced with high fiber intake and routine activities to prevent constipation. Keep in mind that the incidence of constipation in second and third trimester pregnant women is not always seen from the regularity of consuming Fe tablets, but there are other factors that support the occurrence of constipation such as physiological factors due to increased levels of progesterone which causes the intestinal peristaltic to be slow, pressure from the uterus an enlarged intestine, lack of activity, etc.